A boron-nitrogen compound and an organic electroluminescent device thereof
Patent Information
- Application Number
- CN202611316820.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-09
AI Technical Summary
但是就当前OLED显示照明产业的实际需求而言,目前OLED材料的发展还远远不够,落后于面板制造企业的要求,开发基于高发光效率、高器件稳定性、高色纯度的MR-TADF材料,已成为突破当前OLED性能瓶颈的关键路径
本发明提供了一种新型硼氮化合物,通过稠环化策略将苯并咔唑单元与双螺环结构协同引入经典B-N共轭骨架中,实现了“电子结构调控”与“空间构型设计”的双重协同优化。该设计一方面利用苯并咔唑单元的引入显著拓展了共轭骨架,促进电子云离域,提升电荷分布的均匀性,有效提高化合物的光致发光量子效率,进而改善电致发光器件的外量子效率;另一方面,双螺环的引入可有效降低分子振动,实现高色纯度,同时双螺环所赋予的三维立体构型显著增强了分子的空间位阻效应,可有效抑制了固态薄膜中分子间的π–π堆积与非辐射能量转移,削弱因紧密堆积导致的激子猝灭,在进一步提升器件效率的同时,改善器件的寿命。因此,以该类化合物作为发光掺杂材料制备的有机电致发光器件(OLED),在效率、寿命和色纯度方面均具有良好表现,展现出面向下一代高性能显示的应用潜力。
Smart Images

Figure QLYQS_1 
Figure QLYQS_2 
Figure QLYQS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of organic electroluminescent materials technology, specifically relating to a boron nitrogen compound and its organic electroluminescent device. Background Technology
[0002] Organic light-emitting diodes (OLEDs), as the core technology of third-generation displays, have been widely used in various terminal display products such as smartphones, tablets, OLED TVs, automotive displays, and wearable devices due to their outstanding advantages such as self-emission, wide viewing angle, high color gamut, ultra-thin flexibility, high contrast, and fast response. They also have broad application prospects in fields such as solid-state lighting and optoelectronic devices. The key performance characteristics of OLED devices (including luminous efficiency, color purity, lifespan, and power consumption) are directly determined by the molecular structure design of their emissive layer material. Therefore, the research and development of emissive layer materials is a core element in the iterative upgrading and industrialization of OLED technology.
[0003] OLED organic functional layer luminescent materials have undergone three generations of development, all of which have obvious shortcomings: traditional fluorescent materials have extremely low exciton utilization rates, making it difficult to achieve high-efficiency luminescence; although phosphorescent materials have improved luminescence efficiency, they suffer from problems such as efficiency roll-off, dependence on precious metals, and monopoly of core technologies; although traditional DA-type TADF materials have broken free from dependence on precious metals, their color purity is poor and they still cannot meet the requirements of the new generation of ultra-high-definition display standards (BT.2020).
[0004] In recent years, multiple resonance thermo-delayed fluorescence (MR-TADF) materials have shown great potential in achieving high-efficiency, high-color-purity OLEDs due to their high luminous efficiency and narrow emission half-width, attracting widespread attention from the scientific and industrial communities and becoming a research hotspot in the field of organic electroluminescence. However, in terms of the actual needs of the current OLED display and lighting industry, the development of OLED materials is still far from sufficient and lags behind the requirements of panel manufacturers. Developing MR-TADF materials based on high luminous efficiency, high device stability, and high color purity has become a key path to overcome the current performance bottlenecks of OLEDs. Summary of the Invention
[0005] One objective of this invention is to provide an MR-TADF material that effectively improves the luminous efficiency of devices and the lifespan of OLED devices. The technical solution of this invention is as follows: A boron-nitrogen compound having the structure shown in any one of general formulas (1) to (2): ; In the general formula, rings A, B, C, and D are each independently selected from C6-C6. 12 aryl or C5-C 12 heteroaryl groups; R is selected from hydrogen atom, deuterium atom, F atom, deuterated or undeuterated methyl group; R1, R2, R3, and R4 are each independently selected from hydrogen, fluorine, deuterium, cyano, trifluoromethyl, adamantyl, or deuterated or undeuterated C1-C atoms. 10 Alkyl, substituted or unsubstituted C3-C 10 cycloalkyl, substituted or unsubstituted C6-C 18 aryl or C5-C 18 Heteroaryl, substituted or unsubstituted diarylamine, substituted or unsubstituted C6-C 18 arylsilyl group, where n is from 1 to the largest number of substitution sites in the ring; Any two adjacent R1 or adjacent R2 and R3 can connect with each other to additionally form alicyclic or aromatic monocyclic or polycyclic rings; When substitution is present, the substituents are independently selected from F atom, deuterium atom, cyano, trifluoromethyl, deuterated or undeuterated methyl, deuterated or undeuterated isopropyl, deuterated or undeuterated tert-butyl, deuterated or undeuterated phenyl; ---- indicates the presence or absence of a single bond; heteroatoms are N, O, and S.
[0006] As a preferred embodiment of the present invention, rings A, B, C, and D are each independently selected from C6-C6. 12 Aryl groups.
[0007] As a preferred embodiment of the present invention, R1, R2, R3, and R4 are each independently selected from hydrogen atoms, F atoms, deuterium atoms, adamantyl alkyl groups, cyano groups, deuterated or undeuterated C1-C4 alkyl groups, substituted or unsubstituted C6-C groups. 12 aryl or C5-C 12 The heteroaryl, substituted or unsubstituted diarylamine group.
[0008] As a preferred embodiment of the present invention, the specific structure of the boron-nitrogen compound is as follows: ; ; ; ; ; ; ; .
[0009] Another object of the present invention is to provide an organic electroluminescent device comprising an anode, a cathode, and an organic functional layer disposed between the anode and the cathode, the organic functional layer comprising a light-emitting layer, a hole injection layer, a hole transport layer, an electron transport layer, and an electron injection layer, wherein the light-emitting layer comprises at least one of the aforementioned boron nitride compounds.
[0010] Preferably, the light-emitting layer comprises a host material and a dopant material, wherein the dopant material contains the boron-nitrogen compound described in this invention.
[0011] Preferably, the light-emitting layer comprises a host material, a sensitizer, and a dopant material, wherein the dopant material contains the boron-nitrogen compound described in this invention.
[0012] Furthermore, the light-emitting layer comprises a host material, a phosphorus photosensitizer, and a dopant material. The phosphorus photosensitizer is a complex containing a metal element, and the dopant material contains the boron-nitrogen compound described in this invention.
[0013] Preferably, the organic electroluminescent device is used to manufacture display devices, lighting sources, signal lights, and signs, wherein the display devices include mobile phone displays, computer displays, television displays, smartwatch displays, smart car display panels, and VR or AR helmet displays.
[0014] The above lists some specific structural forms of the boron nitrogen compounds described in this invention. However, this invention is not limited to these chemical structures. Any structure based on the structure shown in general formula (1) to general formula (2), where ring A, ring B, ring C, ring D, R, R1, R2, R3, and R4 satisfy the above-mentioned limiting conditions should be included.
[0015] The beneficial effects of this invention are as follows: This invention provides a novel boron-nitrogen compound that, through a fused ring strategy, synergistically introduces benzo[a]carbazole units and a bispiral ring structure into the classic boron-nitrogen (BN) conjugated framework, achieving dual synergistic optimization of "electronic structure regulation" and "spatial configuration design." On the one hand, the introduction of the benzo[a]carbazole units significantly expands the conjugated framework, promotes electron cloud delocalization, improves charge distribution uniformity, and effectively enhances the photoluminescence quantum efficiency of the compound, thereby improving the external quantum efficiency of electroluminescent devices. On the other hand, the introduction of the bispiral ring effectively reduces molecular vibrations, achieving high color purity. Simultaneously, the three-dimensional configuration imparted by the bispiral ring significantly enhances the steric hindrance effect of the molecules, effectively suppressing π–π stacking and non-radiative energy transfer between molecules in solid films, weakening exciton quenching caused by close packing, and further improving device efficiency while also improving device lifetime. Therefore, organic light-emitting diodes (OLEDs) fabricated using this type of compound as a light-emitting dopant exhibit excellent performance in terms of efficiency, lifetime, and color purity, demonstrating application potential for next-generation high-performance displays. Detailed Implementation
[0016] Before providing a detailed description of the invention, it should be understood that the terminology used in this specification is for describing specific embodiments only and is not intended to limit the scope of the invention. The scope of the invention should be defined only by the scope of the appended claims. Unless otherwise expressly stated, all technical and scientific terms used in this specification have the same meaning as commonly understood by one of ordinary skill in the art.
[0017] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the invention and should not be considered as specific limitations thereof. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the protection scope of the present invention.
[0018] Synthesis Examples The present invention does not impose any particular restrictions on the source of the raw materials used in the following embodiments, which can be commercially available products or prepared by methods known to those skilled in the art.
[0019] Example 1: Synthesis of Compound 1 ; Synthesis of 1-3: Under a nitrogen atmosphere, 1-1 (3.82 g, 20.0 mmol), 1-2 (3.06 g, 10.0 mmol), and cesium carbonate (16.3 g, 50.0 mmol) were added to 150 mL of DMF and reacted overnight at 120 °C. Heating was stopped, and after cooling to room temperature, 200 mL of water was added and stirred for 10 min. A large amount of solid precipitated out. The solid was filtered, and the filter cake was washed with ethanol for 2 h. After cooling, the solid was filtered again to obtain 1-3 (5.26 g, 81%). The molecular weight determined by mass spectrometry was 648.63 (theoretical value: 648.78). Synthesis of 1-4: Under a nitrogen atmosphere, 1-3 (3.24 g, 5.0 mmol) was dissolved in a dry THF (50 mL) solution. The mixture was cooled to -78 °C and stirred for 10 min. A hexane solution of n-BuLi (1.6 M, 7.5 mL) was slowly added dropwise. After the addition was complete, the reaction was maintained at low temperature for 1 h. At -78 °C, a THF (30 mL) solution of 9-fluorenone (2.16 g, 12.0 mmol) was slowly added dropwise to the reaction mixture. The mixture was then allowed to warm naturally to room temperature and reacted for 12 h. After the reaction was complete, a small amount of methanol was added to quench the reaction, the solvent was evaporated under reduced pressure, 100 mL of glacial acetic acid and 10 mL of concentrated hydrochloric acid were added, and the mixture was then heated to reflux. After reacting for 2 hours, the mixture was neutralized with saturated sodium carbonate aqueous solution, extracted with dichloromethane and the organic phase was collected. The organic phase was dried with anhydrous sodium sulfate, then filtered and concentrated. The crude product was purified by column chromatography and recrystallized to give compound 1-4 (2.53 g, 62%). The molecular weight determined by mass spectrometry was 815.24 (theoretical value: 815.37). Synthesis of Compound 1: Under a nitrogen atmosphere, 1-4 (2.45 g, 3 mmol) was dissolved in 60 mL of tert-butylbenzene (t-BuPh). After cooling to -78 °C, 7.5 mL of a 1.0 M solution of tert-butyllithium (t-BuLi) in n-pentane was slowly added, followed by stirring at 30 °C for 2 h. The mixture was then cooled again to -78 °C, and 2.25 g, 9 mmol of boron tribromide (BBr3) was slowly added. The reaction mixture was allowed to warm naturally to room temperature and stirred for 1 h. Then, N,N-diisopropylethylamine (DIEA) (1.96 g, 15 mmol) was added, followed by stirring at 130 °C for 12 h. After the reaction was completed, the reaction mixture was cooled to room temperature, methanol was added to the reaction mixture to remove residual boron tribromide, the mixture was separated, extracted with water and dichloromethane, the organic phase was dried with anhydrous sodium sulfate, then filtered and concentrated, the crude product was purified by column chromatography, and recrystallized to give compound 1 (0.83 g, 35%), with a molecular weight determined by mass spectrometry of 788.58 (theoretical value: 788.72).
[0020] Example 2: Synthesis of Compound 3 ; Compound 3 was synthesized using the same method as compound 1, except that 3-1 was used instead of 1-1. All other steps were the same. The molecular mass determined by mass spectrometry was 888.71 (theoretical value: 888.84).
[0021] Example 3: Synthesis of Compound 8 ; Synthesis of 8-3: Under a nitrogen atmosphere, 8-1 (3.49 g, 10.0 mmol), 8-2 (2.68 g, 22.0 mmol), tetrakis(triphenylphosphine)palladium (Pd(PPh3)4) (0.24 g, 0.2 mmol), and potassium carbonate (5.52 g, 40.0 mmol) were placed in a 250 mL three-necked flask, and toluene / ethanol / water = 50 mL / 25 mL / 25 mL was added. The mixture was heated to 60 °C and reacted at this temperature for 12 h. After the reaction system cooled to room temperature, the organic phase was collected by separation, washed with brine, and the aqueous phase was extracted with ethyl acetate. The organic phases were combined, dried with anhydrous magnesium sulfate, filtered, and concentrated. The crude product was purified by column chromatography and recrystallized to obtain 8-3 (2.58 g, 75%). The molecular weight determined by mass spectrometry was 343.31 (theoretical value: 343.43). Compound 8 was synthesized using the same method as compound 1, except that 1-1 was replaced with 8-3. All other steps were the same. The molecular mass determined by mass spectrometry was 1092.97 (theoretical value: 1093.11).
[0022] Example 4: Synthesis of Compound 11 ; Synthesis of 11-3: Under a nitrogen atmosphere, 11-1 (2.46 g, 10.0 mmol) was dissolved in 40 mL of toluene and 10 mL of triethylamine. Then, 11-2 (1.12 g, 11.0 mmol), cuprous iodide (0.38 g, 2.0 mmol), and PdCl2(PPh3)2 (0.70 g, 1.0 mmol) were added. The mixture was heated to reflux for 24 h. After the reaction was completed, the temperature was lowered to room temperature, and the solvent was removed by rotary evaporation. The crude product was purified by column chromatography and recrystallized to obtain 11-3 (1.07 g, 40%). The molecular weight determined by mass spectrometry was 267.18 (theoretical value: 267.33). Synthesis of 11-4: Under a nitrogen atmosphere, 11-3 (2.67 g, 10.0 mmol) was dissolved in 80 mL of nitromethane and 20 mL of THF. Then, copper bromide (3.35 g, 15.0 mmol) and anhydrous potassium carbonate (0.69 g, 5.0 mmol) were added, and the mixture was stirred at room temperature for 12 h. Then, 10 mL of concentrated hydrochloric acid and 10 mL of dichloromethane were added, and the mixture was stirred for 1 h. The organic phase was separated, dried, filtered, and concentrated. The crude product was purified by column chromatography and recrystallized to obtain 11-4 (2.80 g, 81%). The molecular weight determined by mass spectrometry was 346.07 (theoretical value: 346.23). Synthesis of 11-5: Under a nitrogen atmosphere, 11-4 (1.73 g, 5.0 mmol), 8-2 (0.36 g, 6.0 mmol), tetrakis(triphenylphosphine)palladium (Pd(PPh3)4) (60 mg, 0.05 mmol), and potassium carbonate (1.38 g, 10.0 mmol) were placed in a 150 mL three-necked flask, and toluene / ethanol / water = 25 mL / 12.5 mL / 12.5 mL was added. The mixture was heated to 60 °C and reacted at this temperature for 8 hours. After the reaction system cooled to room temperature, the organic phase was collected by separation, washed with brine, and the aqueous phase was extracted with ethyl acetate. The organic phases were combined, dried with anhydrous magnesium sulfate, filtered, and concentrated. The crude product was purified by column chromatography and recrystallized to obtain 11-5 (1.43 g, 83%). The molecular weight determined by mass spectrometry was 343.29 (theoretical value: 343.43). Synthesis of 11-7: Under a nitrogen atmosphere, 11-6 (2.19 g, 10.0 mmol), 1-2 (3.06 g, 10.0 mmol), and cesium carbonate (8.15 g, 25.0 mmol) were added to 100 mL of DMF and reacted overnight at 120 °C. Heating was stopped, and after cooling to room temperature, 100 mL of water was added and stirred for 10 min. A large amount of solid precipitated out. The solid was filtered, and the filter cake was washed with ethanol for 2 h. After cooling, the solid was filtered again to obtain 11-7 (4.15 g, 82%). The molecular weight determined by mass spectrometry was 505.48 (theoretical value: 505.61). The synthesis methods of 11-8 and 11-7 are the same, the difference is that 11-5 is used to replace 11-6 and 11-7 is used to replace 1-2. The molecular mass determined by mass spectrometry is 828.90 (theoretical value: 829.03). Compound 11 was synthesized using the same method as compound 1, except that 1-3 was replaced with 11-8. The other steps were the same. The molecular mass determined by mass spectrometry was 968.84 (theoretical value: 968.97).
[0023] Example 5: Synthesis of Compound 45 ; Compound 45 was synthesized using the same method as compound 1, except that 9-fluorenone was replaced with 45-1. The other steps were the same. The molecular mass determined by mass spectrometry was 988.83 (theoretical value: 988.96).
[0024] Example 6: Synthesis of Compound 59 ; Synthesis of 59-2: Under a nitrogen atmosphere, 11-5 (3.78 g, 11 mmol), 59-1 (2.53 g, 5.0 mmol), copper powder (70.0 mg, 1.1 mmol), iodide ketone (39.0 mg, 0.2 mmol), and potassium carbonate (1.66 g, 12 mmol) were added to 1,4-dioxane (100 mL) and stirred at 90 °C for 18 h. After cooling to room temperature, the mixture was poured into 100 mL of water, extracted with dichloromethane, and the organic phase was collected. The organic phase was dried over anhydrous sodium sulfate, filtered, and concentrated. The crude product was purified by column chromatography and recrystallized to obtain compound 59-2 (3.75 g, 80%). The molecular weight determined by mass spectrometry was 936.55 (theoretical value: 936.72). The synthesis methods of 59-3 and 1-4 are the same, except that 59-2 is used instead of 1-3. The molecular mass determined by mass spectrometry is 1103.19 (theoretical value: 1103.31). Synthesis of 59-4: Under a nitrogen atmosphere, 59-3 (5.52 g, 5.0 mmol) was dissolved in 30 mL of dichloromethane, and NBS (1.07 g, 6.0 mmol) was added. The mixture was stirred at room temperature in the dark for 12 h. After the reaction was complete, the mixture was extracted with water / ethyl acetate, the solvent was removed by rotary evaporation, and 59-4 (3.25 g, 55%) was obtained by silica gel column chromatography. The molecular weight determined by mass spectrometry was 1182.08 (theoretical value: 1182.21). Compound 59 was synthesized using the same method as compound 1, except that 1-4 was replaced with 59-4. The molecular weight determined by mass spectrometry was 1110.95 (theoretical value: 1111.10).
[0025] Example 7: Synthesis of Compound 108 ; Compound 108 was synthesized using the same method as compound 11, except that 108-1 replaced 11-6 and 1-1 replaced 11-5. The other steps were the same. The molecular mass determined by mass spectrometry was 876.76 (theoretical value: 876.91).
[0026] Example 8: Synthesis of Compound 115 ; The synthesis methods of 115-3 and 8-3 are the same, except that 115-1 is used to replace 8-1 and 115-2 is used to replace 8-2. The molecular mass determined by mass spectrometry is 377.40 (theoretical value: 377.53). Synthesis of 115-5: Under a nitrogen atmosphere, 115-3 (1.89 g, 5.0 mmol), 115-4 (2.07 g, 5.0 mmol), tris(dibenzylacetone)dipalladium (Pd2(dba)3) (88 mg, 0.1 mmol), 2-biscyclohexylphosphine-2',4',6'-triisopropylbiphenyl (X-phos) (57 mg, 0.12 mmol), and sodium tert-butoxide (0.53 g, 5.5 mmol) were added to 50 mL of toluene. The reaction mixture was heated to 90 °C and stirred for 8 h. After the reaction was complete, the reaction mixture was cooled to room temperature. Add 50 mL of deionized water to the reaction system, collect the organic phase by separation, dry with anhydrous sodium sulfate, remove the solvent of the organic layer by rotary evaporation, purify the crude product by column chromatography, and recrystallize to obtain 115-5 (2.59 g, 78%), with a molecular weight determined by mass spectrometry of 663.71 (theoretical value: 663.85). The synthesis methods of 115-6 and 11-7 are the same, the difference is that 3-1 is used to replace 11-6 and 115-5 is used to replace 1-2. The molecular mass determined by mass spectrometry analysis is 885.02 (theoretical value: 885.14). Compound 115 was synthesized using the same method as compound 1, except that 1-3 was replaced with 115-6. The other steps were the same. The molecular mass determined by mass spectrometry was 1024.90 (theoretical value: 1025.07).
[0027] Example 9: Synthesis of Compound 132 ; The synthesis methods of 132-3 and 11-5 are the same, the difference being that 11-4 is replaced by 132-1 and 8-2 is replaced by 132-2. The molecular mass determined by mass spectrometry is 432.36 (theoretical value: 432.53). The synthesis methods of 132-4 and 11-7 are the same, the difference being that 11-6 is replaced by 132-3 and 1-2 is replaced by 108-2. The molecular mass determined by mass spectrometry analysis is 978.14 (theoretical value: 978.27). Compound 132 was synthesized using the same method as compound 1, except that 1-3 was replaced with 132-4. The other steps were the same. The molecular mass determined by mass spectrometry was 1118.05 (theoretical value: 1118.20).
[0028] Example 10: Synthesis of Compound 166 ; Synthesis of 166-1: Under a nitrogen atmosphere, 108-3 (3.68 g, 5.0 mmol), 25 mL of heavy water, and 10 mL of toluene were added to a 100 mL three-necked flask and stirred at 120 °C for 24 h. After cooling the reaction system to room temperature, it was extracted three times with dichloromethane and water. After separation, the organic phase was used to remove the solvent using a rotary evaporator to obtain the crude product. The crude product was purified by column chromatography to obtain 166-1 (2.89 g, 75%), with a molecular weight determined by mass spectrometry of 770.06 (theoretical value: 770.18). Compound 166 was synthesized using the same method as compound 1, except that 1-3 was replaced with 166-1. The other steps were the same. The molecular mass determined by mass spectrometry was 905.97 (theoretical value: 906.09).
[0029] Example 11: Synthesis of Compound 193 ; Synthesis of 193-2: Under a nitrogen atmosphere, 11-1 (2.46 g, 10.0 mmol), 11-2 (2.06 g, 10.0 mmol), Pd(dppf)Cl2 (73 mg, 0.1 mmol), and K2CO3 (2.76 g, 20.0 mmol) were added to a mixed solution of 50 mL tetrahydrofuran and 20 mL water. The mixture was refluxed for 4 h. After the reaction was complete, the mixture was allowed to return to room temperature. The organic phase was obtained by filtration, dried over anhydrous magnesium sulfate, and then distilled under reduced pressure. The resulting solid was recrystallized from toluene to give 193-2 (2.13 g, 65%). The molecular weight determined by mass spectrometry was 327.67 (theoretical value: 327.81). Synthesis of 193-3: Under a nitrogen atmosphere, 193-2 (1.64 g, 5.0 mmol), palladium acetate (12 mg, 0.05 mmol), tri-tert-butylphosphine (20 mg, 0.1 mmol), and DBU (1.52 g, 10.0 mmol) were added to 35 mL of DMF and refluxed for 6 h. After the reaction was complete, water was added for reverse precipitation to obtain the crude product. The crude product was recrystallized from toluene to give 193-3 (1.05 g, 72%), with a molecular weight determined by mass spectrometry of 291.19 (theoretical value: 291.35). The synthesis methods for 193-7 and 11-8 are the same, except that 11-6 is replaced by 193-4, 1-2 is replaced by 193-5, and 11-5 is replaced by 193-3. The other steps are the same. The molecular mass determined by mass spectrometry is 766.83 (theoretical value: 766.96). Compound 193 was synthesized using the same method as compound 1, except that 1-3 was replaced by 193-7 and 9-fluorenone was replaced by 193-8. The other steps were the same. The molecular weight determined by mass spectrometry was 962.85 (theoretical value: 963.00).
[0030] Other compounds for which specific synthesis steps are not listed can be prepared using common knowledge in the art, in conjunction with the above examples.
[0031] Device Examples The organic electroluminescent device of the present invention comprises a substrate, an anode, a cathode, and an organic functional layer between the two.
[0032] The substrate described in this invention can be any substrate commonly used in organic electroluminescent devices. The substrate is made of glass or polymer material with excellent mechanical strength, thermal stability, water resistance, and transparency. Furthermore, thin-film transistors (TFTs) can also be incorporated into the substrate used for displays. In this invention, a transparent glass substrate is preferred, and the thickness of the substrate is not particularly limited.
[0033] The anode of this invention can be a transmission electrode, a reflection electrode, or a semi-transmission electrode. When the anode is a transmission electrode, the anode material can be selected from indium tin oxide (ITO), indium zinc oxide (IZO), tin oxide (SnO2), zinc oxide (ZnO), or any combination thereof; when the anode is a semi-transmission electrode or a reflection electrode, the anode material can be selected from magnesium (Mg), silver (Ag), aluminum (Al), aluminum-lithium (Al-Li), calcium (Ca), magnesium-indium (Mg-In), magnesium-silver (Mg-Ag), or any combination thereof.
[0034] The cathode described in this invention can be a transmission electrode, a semi-reflective electrode, or a reflective electrode. When the cathode is a transmission electrode, the cathode material can be selected from transparent metal oxides (e.g., ITO, IZO, etc.); when the cathode is a semi-reflective electrode or a reflective electrode, the cathode material can be selected from Ag, Mg, Cu, Al, Pt, Pd, Au, Ni, Nd, Ir, Cr, Li, Ca, LiF / Ca, LiF / Al, Mo, Ti, compounds including them, or mixtures thereof (e.g., mixtures of Ag and Mg), but is not limited thereto.
[0035] The organic functional material layer between the anode and cathode consists of, from bottom to top, a hole transport region, a light-emitting layer, and an electron transport region.
[0036] The hole transport region of the present invention includes at least one of a hole injection layer (HIL), a hole transport layer (HTL), and an electron blocking layer (EBL), wherein the HIL is located between the anode and the HTL, and the EBL is located between the HTL and the light-emitting layer.
[0037] As for the materials used in the hole injection layer, hole transport layer, and electron blocking layer, any material can be selected from known materials used in organic electroluminescent devices.
[0038] The hole injection layer described in this invention can be a single-layer structure composed of a single substance, or a single-layer or multi-layer structure composed of different substances and processes, preferably a material with good hole-accepting ability. It can be selected from materials such as metalloporphyrin compounds, oligothiophene and its derivatives, arylamine compounds, hexanitrile hexaazabenzophenanthrene compounds, perylene compounds, etc., but is not limited thereto.
[0039] The hole transport layer described in this invention can be a single-layer structure composed of a single material, or a single-layer or multi-layer structure composed of different materials, preferably a material with high hole mobility. It can be selected from materials such as diphenylamine compounds, fluorene compounds, carbazole compounds, and aromatic amine derivatives, but is not limited thereto.
[0040] The electron blocking layer described in this invention can prevent or reduce the injection of electrons from the electron transport region into the hole transport region. It can be selected from carbazole derivatives, fluorene derivatives, N,N'-bis(3-methylphenyl)-N,N'-diphenyl-[1,1'-biphenyl]-4,4'-diamine (TPD), triphenylamine derivatives, N,N'-bis(naphthyl-1-yl)-N,N'-diphenyl-benzidine (NPB), 4,4'-cyclohexylene-bis[N,N-bis(4-methylphenyl)aniline] (TAPC), etc., but is not limited thereto.
[0041] The light-emitting layer of the present invention comprises a doping material, a host material, and a sensitizer, and a dual host material formed by two host materials can be used.
[0042] The doping material uses boron-nitrogen compounds represented by the general formula of this invention.
[0043] The host material not only needs to possess bipolar charge transport properties, but also requires appropriate energy levels to effectively transfer excitation energy to the doped material. Preferred host materials include heterocyclic compounds, metal complexes, and aromatic amine compounds, but are not limited to these.
[0044] Sensitizers are materials that enable the luminescent materials in the light-emitting layer to fully utilize electroexcitons. In organic light-emitting devices (OLEDs), they may perform functions such as exciton capture, exciton conversion, and exciton transfer, thereby improving the performance of OLED devices. Sensitizers are mainly classified into phosphorescent sensitizers, TADF sensitizers, and excitocomplex sensitizers. Examples of phosphorescent sensitizers include iridium complexes and platinum complexes. TADF sensitizers primarily use TADF materials. Excitocomplex sensitizers consist of donor and acceptor materials.
[0045] The electron transport region of the present invention includes at least one of an electron injection layer (EIL), an electron transport layer (ETL), and a hole blocking layer (HBL), wherein the EIL is located between the cathode and the ETL, and the HBL is located between the ETL and the light-emitting layer.
[0046] The electron injection layer described in this invention can be a monolayer structure composed of a single substance, or a monolayer or multilayer structure composed of different substances. Preferably, it is a material with a low work function, allowing electrons to be easily injected into the organic functional material layer. The material can be selected from Li, Ca, Sr, LiF, CsF, CaF2, BaO, Li2CO3, CaCO3, Li2C2O4, Cs2C2O4, CsAlF4, LiOx, Yb, Tb, cesium 8-hydroxyquinoline, tris(8-hydroxyquinoline)aluminum, etc., but is not limited to these.
[0047] The electron transport layer described in this invention can be a monolayer structure composed of a single material, or a monolayer or multilayer structure composed of different materials, preferably a material with high electron mobility. It can be selected from materials such as quinolines, imidazoles, o-phenanthroline compounds, triazoles, metal chelates, azirbenzene derivatives, diazanthracene derivatives, boron-containing heterocyclic compounds, cyano compounds, benzimidazoles, etc., but is not limited thereto.
[0048] The hole-blocking layer described in this invention can be a single-layer structure composed of a single material, or a single-layer or multi-layer structure composed of different materials. It can be selected from aluminum complexes, lithium complexes, beryllium complexes, oxazole derivatives, benzoxazole derivatives, thiazole derivatives, benzothiazole derivatives, imidazole derivatives, benzimidazole derivatives, phenanthroline derivatives, etc., but is not limited thereto.
[0049] The thickness of each of the aforementioned organic layers is typically between 1 nanometer and 100 micrometers, preferably between 5 nanometers and 1000 nanometers, and more preferably between 5 nanometers and 200 nanometers. The thickness of the anode and cathode is adjusted according to the required transparency.
[0050] The organic functional layer of the aforementioned organic electroluminescent device can be deposited by vacuum deposition, spin coating, casting, etc. When using vacuum deposition, the conditions for vacuum deposition vary depending on the compound.
[0051] The organic electroluminescent device of the present invention may further include an encapsulation structure. The encapsulation structure may be a protective structure preventing external substances such as moisture and oxygen from entering the organic layer of the organic electroluminescent device. The encapsulation structure may be a glass container or a metal container; or a thin film covering the entire surface of the organic layer.
[0052] The following detailed description of the application effects of the boron nitride compound of the present invention in organic electroluminescent devices is provided through device examples 1-11 and device comparative examples 1-2. The device examples and device comparative examples of the present invention are manufactured using the same process, and employ the same substrate and electrode materials, with consistent electrode film thickness. The only difference is the replacement of the doping material in the light-emitting layer. However, it should be noted that the following detailed description is not intended to limit the present invention, and those skilled in the art can extend its application to other organic electroluminescent devices.
[0053] The structures of other compounds used in the device embodiments besides the boron-nitrogen compounds described in this invention are as follows: .
[0054] Device Example 1 An organic electroluminescent device includes an anode (ITO), a hole injection layer, a hole transport layer, an electron blocking layer, a light-emitting layer, a hole blocking layer, an electron transport layer, an electron injection layer, and a cathode, which are sequentially stacked. The fabrication method of the organic electroluminescent device is as follows: (1) Substrate treatment: Transparent ITO glass was used as the substrate for preparing electroluminescent devices. It was first ultrasonically treated with 5% ITO washing solution for 30 min, and then ultrasonically washed with distilled water (2 times), acetone (2 times), and isopropanol (2 times) in sequence. It was baked in a clean environment until the solvent was completely removed, cleaned with ultraviolet light and ozone, and bombarded with low-energy cation beam. (2) The device is fabricated using a vacuum deposition equipment with a vacuum evaporation process. The glass substrate is placed in the vacuum chamber of the evaporation equipment. When the vacuum degree of the vacuum evaporation system reaches 5×10 -4 Evaporation begins when Pa is below 1. (3) The following layers are deposited layer by layer on a transparent ITO glass substrate: 1) HI-1 and HT-1 (mass ratio of 3:97) as hole injection layer with a thickness of 10 nm; 2) HT-1 as hole transport layer with a thickness of 60 nm; 3) EB-1 as electron blocking layer with a thickness of 5 nm; 4) The light-emitting layer adopts phosphorescence luminescence technology, using GH-1 and GH-2 as host materials, GD-1 as phosphorescence sensitizer, and compound 1 as dopant material. The mass ratio of GH-1, GH-2, GD-1 and compound 1 is 60:40:6:1, and the thickness of the light-emitting layer is 35 nm; 5) HB-1 as hole blocking layer with a thickness of 5 nm; 6) ET-1 and Liq (mass ratio of 1:1) as electron transport layer with a thickness of 30 nm; 7) LiF as electron injection layer with a thickness of 1 nm; 8) Al as cathode with a thickness of 100 nm. The total evaporation rate of all organic layers and LiF was controlled at 0.1 nm / s, and the evaporation rate of the metal electrode was controlled at 0.4 nm / s. (4) Packaging: The device is encapsulated in a nitrogen glove box with UV-cured resin.
[0055] Device Examples 2-11, Device Comparative Examples 1-2 An organic electroluminescent device is disclosed, which differs from device example 1 only in that the doping materials of the light-emitting layer are the compounds shown in Table 1; the other layers, thicknesses, materials, and preparation methods are the same as those in device example 1.
[0056] The organic electroluminescent devices prepared by the above process were subjected to the following performance measurements: Under the same brightness, using a photoelectric testing system integrating a Keithley 2400 source meter and a spectrometer, the JVL characteristics and electroluminescence spectra of the organic electroluminescent devices prepared in Device Examples 1-11 and Comparative Examples 1-2 were tested at room temperature. A constant current of 10 mA / cm² was maintained. 2The external quantum efficiency (EQE) of the device was measured. The EQE was calculated using current density, luminance, and electroluminescence spectrum combined with the apparent function, assuming a Lambaugh distribution of light emission. Lifetime testing was performed using the OLED lifetime testing system from Suzhou Fosstar Scientific Instruments Co., Ltd. Device lifetime (LT95) refers to the time taken at a current density of 50 mA / cm². 2 The time required for the device brightness to decrease to 95% of its initial brightness under certain conditions. External quantum efficiency and lifetime are relative values (device performance is compared to Comparative Example 1, where all performance indicators are set to 1.00). Detailed data are shown in Table 1. ; As can be seen from Table 1 above, compared with Comparative Example 1 and Comparative Example 2, the electroluminescent device prepared by using the compound of the present invention as the doping material of the light-emitting layer exhibits significantly better overall performance, with higher external quantum efficiency and longer lifetime.
[0057] The above embodiments only list the effect data of devices made from a portion of the structures. This is a representative sampling test. Based on the experimental data, the overall data is not significantly different and can represent the effects of other unlisted structures.
[0058] Those skilled in the art will readily recognize that many modifications and variations can be made to this invention without departing from its spirit and scope. Therefore, it is contemplated that this invention covers the modifications and variations provided within the scope of the appended claims and their equivalents.
[0059] The applicant declares that the organic electroluminescent material and organic electroluminescent device of the present invention are illustrated through the above embodiments, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A boron-nitrogen compound, characterized in that, Its structure is shown in any one of general formulas (1) to (2): ; In the general formula, rings A, B, C, and D are each independently selected from C6-C6. 12 aryl or C5-C 12 heteroaryl groups; R is selected from hydrogen atom, deuterium atom, F atom, deuterated or undeuterated methyl group; R1, R2, R3, and R4 are each independently selected from hydrogen, fluorine, deuterium, cyano, trifluoromethyl, adamantyl, or deuterated or undeuterated C1-C atoms. 10 Alkyl, substituted or unsubstituted C3-C 10 cycloalkyl, substituted or unsubstituted C6-C 18 aryl or C5-C 18 Heteroaryl, substituted or unsubstituted diarylamine, substituted or unsubstituted C6-C 18 arylsilyl group, where n is from 1 to the largest number of substitution sites in the ring; Any two adjacent R1 or adjacent R2 and R3 can connect with each other to additionally form alicyclic or aromatic monocyclic or polycyclic compounds; When substitution is present, the substituents are independently selected from F atom, deuterium atom, cyano, trifluoromethyl, deuterated or undeuterated methyl, deuterated or undeuterated isopropyl, deuterated or undeuterated tert-butyl, deuterated or undeuterated phenyl; ---- indicates the presence or absence of a single bond; heteroatoms are N, O, and S.
2. The boron-nitrogen compound according to claim 1, characterized in that, Rings A, B, C, and D are each independently selected from C6-C6. 12 Aryl groups.
3. The boron-nitrogen compound according to claim 1, characterized in that, R1, R2, R3, and R4 are each independently selected from hydrogen, F, deuterium, adamantyl, cyano, deuterated or undeuterated C1-C4 alkyl, substituted or unsubstituted C6-C. 12 aryl or C5-C 12 The heteroaryl, substituted or unsubstituted diarylamine group.
4. The boron-nitrogen compound according to claim 1, characterized in that, The specific structure of this compound is as follows: ; ; ; ; ; ; ; 。 5. An organic electroluminescent device, comprising an anode, a cathode, and an organic functional layer disposed between the anode and the cathode, the organic functional layer comprising a light-emitting layer, a hole injection layer, a hole transport layer, an electron transport layer, and an electron injection layer, characterized in that, The light-emitting layer comprises at least one of the boron nitrogen compounds according to any one of claims 1 to 4.
6. The organic electroluminescent device according to claim 5, wherein the light-emitting layer comprises a host material and a guest material, characterized in that, The guest material comprises at least one of the boron nitrogen compounds according to any one of claims 1 to 4.
7. The application of the organic electroluminescent device according to any one of claims 5-6 in an organic electroluminescent display or an organic electroluminescent lighting source.